Inside Back Cover: A Smart Photosensitizer–Manganese Dioxide Nanosystem for Enhanced Photodynamic Therapy by Reducing Glutathione Levels in Cancer Cells (Angew. Chem. Int. Ed. 18/2016). Issue 18 (24th March 2016) - Fan, Huanhuan; Yan, Guobei; Zhao, Zilong; Hu, Xiaoxiao; Zhang, Wenhan; Liu, Hui; Fu, Xiaoyi; Fu, Ting; Zhang, Xiao‐Bing; Tan, Weihong
Abstract : A smart photosensitizer–MnO2 nanosystem has been developed to enhance photodynamic therapy by reducing glutathione (GSH) levels in cancer cells. In their Communication on page 5477 ff, W. Tan and co‐workers show that this nanosystem could deplete intracellular GSH and generate singlet oxygen in the presence of light irradiation, thus increasing its efficiency in killing cancer cells. The picture depicts the system in the form of a computer game.